2022
DOI: 10.1039/d2qm00770c
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic acid based metal–organic frameworks with dual function of NADH peroxidase and glycerol dehydrogenase-mimicking activities

Abstract: CuAsp with a fiber-like structure exhibited both NADH peroxidase- and glycerol dehydrogenase (GlyDH)-mimetic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In a separate study, Liu et al. [ 31 ] synthesized copper aspartic acid (CuAsp) metal‐organic frameworks (MOFs) by altering the functional groups of ligands and observed that both the length of the carbon chain and the number of amino groups in the ligands influenced the catalytic activity. The results demonstrated that CuAsp MOF exhibited the highest catalytic activity when L‐aspartic acid was used as the ligand, owing to the strong coordination ability of L‐aspartic acid with Cu 2+ .…”
Section: Classification Of Cu‐based Nanozymes and Catalytic Mechanismmentioning
confidence: 99%
“…In a separate study, Liu et al. [ 31 ] synthesized copper aspartic acid (CuAsp) metal‐organic frameworks (MOFs) by altering the functional groups of ligands and observed that both the length of the carbon chain and the number of amino groups in the ligands influenced the catalytic activity. The results demonstrated that CuAsp MOF exhibited the highest catalytic activity when L‐aspartic acid was used as the ligand, owing to the strong coordination ability of L‐aspartic acid with Cu 2+ .…”
Section: Classification Of Cu‐based Nanozymes and Catalytic Mechanismmentioning
confidence: 99%
“…L-Aspartic acid (ASP) is regarded as a suitable linker, which not only provides flexibility and donates electrons to the metal in the framework, but also presents optical activity, enabling the preparation of chiral materials. [23][24][25] The benefits of utilizing this functional biomolecule include its multiple coordination sites, hydrogen bonding, aliphatic backbone, and chirality. [26][27][28] Furthermore, the natural abundance and com-mercial availability of L-aspartic acid make it an appropriate multifunctional molecule for the preparation of bioMOFs.…”
Section: Introductionmentioning
confidence: 99%
“…32 Also, because the uncoordinated amino groups pointed toward the pores, MIP-202(Zr) presented different behavior from that of the Zr-fumarate compound as a Lewis base and Brønsted acid. 24 The Brønsted acidity of MIP-202 originated from the conversion of the NH 2 group of l -aspartic acid to NH 3 + under acidic condition. Indeed, because of the production of HCl upon the hydrolysis of ZrCl 4 , the NH 3 + Cl − -ASP salt moiety was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Connected and extended through coordination bonds between metal ions and organic ligands, MOFs share similarities with natural enzymes in terms of size, morphology, and surface charge. [33][34][35] Additionally, MOFs can mimic the structure of the active center of natural metalloenzymes. [36][37][38][39] Iron-based catalysts have attracted attention due to their low toxicity and low cost.…”
Section: Introductionmentioning
confidence: 99%